2001
DOI: 10.1177/104973150101100303
|View full text |Cite
|
Sign up to set email alerts
|

Reintegration Services and the Likelihood of Adult Imprisonment: A Longitudinal Study of Adjudicated Delinquents

Abstract: Objective: This study used longitudinal data to identify the factors associated with adult imprisonment for adjudicated delinquent males following long-term residential care. Method: Logistic regression and survival models were developed to examine the effectiveness of reintegrational services. The sample included 397 adjudicated delinquents released between 1992 and 1993 from a residential treatment facility in Michigan. The Michigan Department of Corrections provided incarceration data approximately 5 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 18 publications
4
14
0
1
Order By: Relevance
“…5 Consistent with the literature, four delinquent history variables were significant and positively related to the odds of rearrest: the total number of delinquent adjudications prior to state commitment (Lattimore et al, 2004;Ryan et al, 2001;Trulson et al, 2005;Weibush et al, 2005), being a homicide-related offender, being gang affiliated (Benda et al, 2001a, 2001b, Lattimore et al, 2004Trulson et al, 2005;Wiebush et al, 2005), and having perpetrated a gang-related commitment offense. Offenders who engaged in assaultive activity in YCS and those with a higher infraction rate/year were also significantly more likely to be rearrested for any offense postrelease, net the effects of other variables in the model (Lattimore et al, 2004;Trulson et al, 2005).…”
Section: Relationship Of Variables To Rearrest For Any Offensesupporting
confidence: 67%
See 2 more Smart Citations
“…5 Consistent with the literature, four delinquent history variables were significant and positively related to the odds of rearrest: the total number of delinquent adjudications prior to state commitment (Lattimore et al, 2004;Ryan et al, 2001;Trulson et al, 2005;Weibush et al, 2005), being a homicide-related offender, being gang affiliated (Benda et al, 2001a, 2001b, Lattimore et al, 2004Trulson et al, 2005;Wiebush et al, 2005), and having perpetrated a gang-related commitment offense. Offenders who engaged in assaultive activity in YCS and those with a higher infraction rate/year were also significantly more likely to be rearrested for any offense postrelease, net the effects of other variables in the model (Lattimore et al, 2004;Trulson et al, 2005).…”
Section: Relationship Of Variables To Rearrest For Any Offensesupporting
confidence: 67%
“…Other relatively recent studies have examined offender characteristics and recidivism among samples of released state incarcerated delinquents (Benda, Corwyn, & Toombs, 2001a, 2001bRyan, Davis, & Yang, 2001). As opposed to rearrest indicators, in each of the studies incarceration or sanctioning in the adult correctional system was the measure of recidivism.…”
Section: Release Recidivism and Institutionalized Delinquentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further exploration in the adjusted model, which included both sociodemographic and socioeconomic categories, showed that the odds of coming in contact with the criminal justice system increased for those Black adults who were experiencing family and financial stressors but decreased for those who reported experiencing neighborhood and personal stressors. Other studies have postulated that a person’s life stressors are linked to an increased probability of having contact with the criminal justice system (Hochstetler, Murphy, & Simons, 2004; Ryan, Davis & Yang, 2001; Greene, Haney & Hurtado, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Vissa studier indikerar att en integrerad organisation har fördelar i jämförelse med en specialiserad när det gäller stöd-och behandlingsinsatser (Cambridge & Parkes 2006, Cambridge et al 2011, Fuller & Tulle-Winton 1996, Marsh et al 2005, Astvik & Aronsson 1999. Det har visat sig fördelaktigt med organisationer som har kompetens och mandat att uppmärksamma klienters totala livssituation vid förändringsarbete, trots att kontakten initierats utifrån snävare problemområden som exempelvis försörjningsproblem (Marttila et al 2012), ungdomar med komplexa behov (Ungar et al 2012), eller ungdomskriminalitet (Ryan et al 2001). När det gäller förutsättningarna för att utveckla bärande relationer mellan socialarbetare och klient visar vissa studier att den integrerade organisationen är mer fördelaktig (Perlinski 2010).…”
Section: Helhetssyn -Ett Svårfångat Men Grundläggande Argument För Inunclassified